(untitled) (Research, Society and Development, 2020)
That article has the aim to analyse the Brazilian National Program for the Integration of Professional Education with Basic Education in the Youth and Adult Education Modality (PROEJA), considering its implementation in society, whose constitution was due to the permanence of patrimonial-bureaucratic systems. The methodological procedure used was the documentary research carried out through the analysis of Decree No. 5,840, of July 13, 2006, which instituted PROEJA at the federal level. Theoretical sources that deal with aspects pertinent to the research object were also used to support the study. The results demonstrate that this legal norm provides the insertion of these students in educational institutions. However, the hybrid model of patrimonialism and bureaucracy hinders substantial changes, since the attempt to implement the Program in the Federal Institutions of Professional and Technological Education, are opposed to the traditional values and practices of teachers. It is concluded that the actions recommended for the realization of this educational proposal can constitute effective strategies to destabilize patrimonial practices, enabling the fulfillment of the Program in school institutions.